One-pot transformation of furfural into γ-valerolactone catalyzed by a hierarchical Hf-Al-USY zeolite with balanced Lewis and Brønsted acid sites. Issue 18 (24th August 2021) - Tang, Bo; Li, Shuang; Song, Wei-Chao; Li, Yan; Yang, En-Cui
Abstract : A hierarchically structured bifunctional Hf-Al-USY zeolite with balanced Lewis and Brønsted acid sites has been developed as a robust catalyst for the one-pot conversion of biomass-derived furfural to γ-valerolactone. Abstract : The upgrading of furfural to high value-added chemicals is currently an attractive and challenging route in biorefineries. Herein, a hierarchically structured bifunctional Hf-Al-USY zeolite with balanced Brønsted and Lewis acid sites has been developed as a robust catalyst for the one-pot conversion of furfural (FA) to γ-valerolactone (GVL). The Hf-Al-USY zeolite was fabricated through a two-step post-synthesis procedure consisting of precisely controlled dealumination of parent H-USY and incorporation of framework Hf sites. Intensive characterization results from XRD, TEM, UV-vis, XPS, DRIFT and FTIR spectroscopy of pyridine adsorption verified the coexistence of Brønsted and Lewis acid sites within the single Hf-Al-USY zeolite. Due to the synergistic effect of the hydrolytic ring-opening reaction (by Brønsted acidity from the Al sites) and H-transfer hydrogenation reaction (by Lewis acidity from the Hf sites) as well as improved mass transfer (by the dealumination-induced hierarchical structure), the as-synthesized Hf-Al-USY demonstrated remarkably high performance in the one-pot production of GVL from FA. In recycling experiments, the Hf-Al-USY zeolite showed good recyclability upon a thermal calcination treatment. In addition, a possible reaction pathway was proposed for the one-pot conversion of FA to GVL.